The role of selected Indonesian and Philippine Academic Libraries amidst fake news - Thoriq Tri Prabowo; April Ramos Manabat (Jurnal Kajian Informasi dan Perpustakaan, 2021)
People now have easy access to information on the internet, but people find it difficult to find valid information. Librarians in academic environments have a huge task in helping users receive the correct information. Several university academic libraries in Indonesia and the Philippines play a role in providing insight into false information. This study aimed to describe the information literacy program in several university libraries in Indonesia and the Philippines, selected purposively. The research method used descriptive qualitative research with data collection techniques using questionnaires sent to six libraries from two countries. Based on the study results, six libraries from two countries fought fake news by validating information and checking trusted sources from the academic community. Libraries included the Information Literacy Program in lectures to practice critical thinking skills, used information responsibly, disseminated and preserved information, primarily through social media. Academic libraries applied various strategies and methods to teach information literacy to students through fun and engaging lectures, seminars, workshops, and interactive games. Libraries establish communication with librarians, students, lecturers, and universities. Indonesian and Philippine academic libraries effectively use the Information Literacy Program to educate, protect against access and dissemination of false information. The study results can be used as additional literature in information literacy in both ASEAN countries and the movement to eradicate fake news worldwide.